Cytology diagnostic principles and clinical correlates - Cibas, Edmund S.; Ducatman, Barbara S. (Elsevier Saunders, 2014)
Fully updated, the 4th edition of Cytology helps you apply the latest diagnostic techniques for the interpretation of a complete range of cytological specimens. This medical reference book offers you quick access to the newest methods and adjunct tests, all in a brief, highly readable format that makes quick work of reviewing the key information available on this powerful yet minimally invasive method. It's a perfectly practical bench manual for trainees and practicing pathologists alike!